CLCN7 and TCIRG1 Mutations Differentially Affect Bone Matrix Mineralization in Osteopetrotic Individuals. (April 2014) - Barvencik, Florian; Kurth, Ingo; Koehne, Till; Stauber, Tobias; Zustin, Jozef; Tsiakas, Konstantinos; Ludwig, Carmen F; Beil, F Timo; Pestka, Jan M; Hahn, Michael; Santer, Rene; Supanchart, Chayarop; et al.
ABSTRACT Osteopetrosis is an inherited disorder of impaired bone resorption, with the most commonly affected genes being CLCN7 and TCIRG1, encoding the Cl−/H+ exchanger CLC‐7 and the a3 subunit of the vacuolar H+‐ATPase, respectively. We and others have previously shown that the disease is frequently accompanied by osteomalacia, and that this additional pathology is also found in Tcirg1‐deficient oc/oc mice. The remaining question was whether osteoid enrichment is specifically associated with TCIRG1 inactivation, or whether CLCN7 mutations would also cause skeletal mineralization defects. Here we describe a complete osteologic assessment of one family carrying a novel mutation in CLCN7 (D145G), which impairs the activation and relaxation kinetics of the CLC‐7 ion transporter. The two siblings carrying the mutation in the homozygous state displayed high bone mass, increased serum levels of bone formation markers, but no impairment of calcium homeostasis when compared to the other family members. Most importantly, however, undecalcified processing of an iliac crest biopsy from one of the affected children clearly demonstrated a pathological increase of trabecular bone mass, but no signs of osteomalacia. Given the potential relevance of these findings we additionally performed undecalcified histology of iliac crest biopsies from seven additional cases with osteopetrosis caused by a mutation in TNFRSF11A (n = 1), CLCN7 (n = 3), or TCIRG1 (n = 3). Here we observed that all cases with TCIRG1‐dependent osteopetrosis displayed severe osteoid accumulation and decreased calcium content within the mineralized matrix. In contrast, there was no detectable bone mineralization defect in the cases with TNFRSF11A‐dependent or CLCN7‐dependent osteopetrosis. Taken together, our analysis demonstrates that CLCN7 and TCIRG1 mutations differentially affect bone matrix mineralization, and that there is a need to modify the current classification of osteopetrosis. © 2014 American Society for Bone and Mineral Research.